Mussel-Inspired Cellulose Nanocomposite Tough Hydrogels with Synergistic Self-Healing, Adhesive, and Strain-Sensitive Properties - Shao, Changyou; Wang, Meng; Meng, Lei; Chang, Huanliang; Wang, Bo; Xu, Feng; Yang, Jun; Wan, Pengbo (Chemistry of materials, 2018)
The remarkable progress in efforts to prepare conductive self-healing hydrogels mimicking human skin’s functions has been witnessed in recent years. However, it remains a great challenge to develop an integrated conductive gel combining excellent self-healing and mechanical properties, which is derived from their inherent compromise between the dynamic cross-links for healing and steady cross-links for mechanical strength. In this work, we design a tough, self-healing, and self-adhesive ionic gel by constructing synergistic multiple coordination bonds among tannic acid-coated cellulose nanocrystals (TA@CNCs), poly(acrylic acid) chains, and metal ions in a covalent polymer network. The incorporated TA@CNC acts as a dynamic connected bridge in the hierarchically porous network mediated by multiple coordination bonds, endowing the ionic gels the superior mechanical performance. Reversible nature of dynamic coordination interactions leads to excellent recovery property as well as reliable mechanical and electrical self-healing property without any assistance of external stimuli. Intriguingly, the ionic gels display durable and repeatable adhesiveness ascribed to the presence of catechol groups from the incorporated tannic acid, which can be adhered directly on human skin without inflammatory response and residual. Additionally, the ionic gels with a great strain sensitivity can be employed as flexible strain sensors to monitor and distinguish both large motions (e.g., joints bending) and subtle motions (e.g., pulse and breath), which enable us to analyze the data on the user interface of smart phone via programmable wireless transmission. This work provides a new prospect for the design of the biocompatible cellulose-based hydrogels with stretchable, self-adhesive, self-healing, and strain-sensitive properties for potential applications in wearable electronic sensors and healthcare monitoring.